Molecular Mechanism Behind the Capture of Fluorinated Gases by Metal–Organic Frameworks - Qian Wang; Yong Hu; Yifan Gu (Nano-Micro Letters)
Highlights The progress of metal–organic frameworks (MOFs) in capturing and separating F-gases is highlighted. The molecular mechanisms of adsorption and separation are classified and analyzed. Toolboxes of MOFs structural design for fluorinated gases separation are provided.